2007
DOI: 10.1017/s0043933907001638
|View full text |Cite
|
Sign up to set email alerts
|

Wheat value: improvements by feed technology, plant breeding and animal genetics

Abstract: Wheat is a common ingredient in poultry diets, especially in Europe. Due to its low protein and high starch levels, wheat is essentially used as an energy supplier. Nutritional values of wheat samples vary according to their nutrient content and digestibilities. Variations of nutrient contents may be associated with cultivars and environmental conditions. Digestibility variations in growing chicks may be associated with these factors, and also, with technological treatments of diets and genetic origin of birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Carré et al (2002) reported that in broilers, high digesta viscosity negatively affected lipid and starch digestibility, while the digestibility of protein of different wheat cultivars was similar. Carré et al (2007) stressed that the viscosity of wheat in the chicken digestive tract results from a combination of several variables, among others from the physico-chemical characteristics of soluble NSP, endogenous xylanases, activity of proteinaceaous inhibitors, and technological treatment (grinding, pelleting).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carré et al (2002) reported that in broilers, high digesta viscosity negatively affected lipid and starch digestibility, while the digestibility of protein of different wheat cultivars was similar. Carré et al (2007) stressed that the viscosity of wheat in the chicken digestive tract results from a combination of several variables, among others from the physico-chemical characteristics of soluble NSP, endogenous xylanases, activity of proteinaceaous inhibitors, and technological treatment (grinding, pelleting).…”
Section: Discussionmentioning
confidence: 99%
“…At least several hundred wheat cultivars are used throughout the world, however, most of the technological parameters that describe the quality of seeds have been defi ned for human utilization (Carré et al, 2007). In Europe wheat is commonly used in poultry diets, but the nutritional potential of wheat cultivars in poultry feeding remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D 1 and D 2 chicken lines were developed because it appeared that the overall variability in digestion efficiencies in growing chickens fed various wheat diets came largely from individual birds, and much less came from wheat samples (Choct et al, 1999;McCracken et al, 2001;Carré et al, 2002 and. Therefore, genetic selection appeared to be an efficient way to improve digestion efficiency in growing chickens fed on wheat diets (Mignon-Grasteau et al, 2004;Carré et al, 2007). Besides such economic interest, D 1 and D 2 lines also represent a unique model for the study of physiological and genetic limiting factors of digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Its nutritional potential in feeding birds is not well known due to the variability of energy values among its cultivars (CARRÉ et al, 2007). Triticale is obtained by artificially crossing wheat with rye, and has a higher protein and lower fiber content compared with wheat bran.…”
Section: Introductionmentioning
confidence: 99%